Appreciation to peer-reviewers 2019 - Pacheco-Romero, José (2019)
The Editorial Committee of the Peruvian Journal of Gynecology and Obstetrics (RPGO) thanks the renowned professionals, researchers and academics who contributed selflessly and promptly in the evaluations of the articles published in the RPGO Volume 65 numbers 1, 2, 3 and 4 during the year 2019, by peer review.